Tropical cyclone activity over the North Indian Ocean - Mohapatra, M.; Bandyopadhyay, B. K.; Rathore, L. S. (Springer, 2017)
This book deals primarily with understanding, monitoring and prediction of Tropical Cyclones (TCs) over the North Indian Ocean (NIO). There is special emphasis on TC genesis, intensification, movement and associated adverse weather like heavy rainfall and gale winds. It highlights the current state of research on TCs over the NIO and recent improvements in early warning systems due to advances in observational, analytical and numerical weather prediction techniques. The chapters in the book are authored by leading experts from research and operational environments. The chapters presented in the book intend to stimulate thinking and hence further research in the field of TCs, especially over the NIO region. They provide high quality reference material for all experts working in the field of TC related disaster management. This book is relevant to TC forecasters and researchers, managers, policy makers, graduate and undergraduate students.- Resumé vydavatel